Implementation Of Accounting In Oyster Mushroom Cultivation Business In Mushroom House, Margomulyo Village, Banyuwangi Regency From Islamic Economic Perspective - Kiptiyah, Rifatul; Siswanto, Adil (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This Public Service aims to find out the implementation of financial reports in oyster mushroom cultivation businesses at Rumah Jamur, Margomulyo Village, Banyumas Regency and to find out the implementation of accounting in mushroom cultivation businesses at Rumah Jamur from an Islamic economic perspective. Method: The method used in conducting this research is a qualitative method. Data collection techniques in this study include observation, interviews and documentation. The results of this study are that oyster mushroom cultivation businesses still apply simple financial reports, namely only recording cash income and expenses. Practical Applications: Oyster mushrooms are an agricultural commodity that if not managed properly will quickly wilt or rot. Because mushrooms are horticultural products that continue to undergo metabolism and respiration after being harvested, post-harvest management needs to be carried out immediately to prevent losses. Without further treatment, fresh oyster mushrooms in Margomulyo stored at room temperature can be damaged and unfit for human consumption in just one to two days. To overcome this, producers package their mushrooms to increase their shelf life. Conclusion: The implementation of Accounting Financial Reports in oyster mushroom cultivation businesses is still considered not in accordance with applicable standards, due to minimal knowledge and lack of resources and training on accounting standards. Therefore, training on broader accounting standards is needed in these businesses.